A Short Guide and a Forest Plot Command (Ipdforest) for One-Stage Meta-Analysis. (September 2013) - Kontopantelis, Evangelos; Reeves, David
In this article, we describe a new individual patient data meta-analysis postestimation command, ipdforest . The command produces a forest plot following a one-stage meta-analysis withxtmixed orxtmelogit . (These commands have been renamed in Stata 13 tomixed andmeqrlogit, respectively;ipdforest is currently not compatible with the new names.) The overall effect is obtained from the preceding mixed-effects regression and the study effects from linear or logistic regressions on each study, which are executed withinipdforest . Individual patient data meta-analysis models with Stata are discussed.